ICTs in the classroom: case study Colombia - Cipagauta Moyano, Marisol Esperanza (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
A study conducted in partnership with Blinklearning and several organizations, including UNIMINUTO, showed interesting results to consider when using technology. 1,014 teachers of Primary, Secondary and University levels were surveyed. The main categories of the study are: usage of ICTs, the digitalization of educational centers, post COVID impact, teaching role and a general vision of education. These categories are the basis of this article, which aims to show the current situation from the point of view of the protagonists, Colombian teachers from the different educational levels.